Professional Development Training Based-Innovation Technology and Pedagogy for Vocational English Language Teachers - Wijaya, Beni; Zakaria, Zakaria; Darmaliana, Darmaliana; Kusmartini, Sri Endah; Yeny, Eli; Rienvillia, Nafizsha Donna; Alditria, Amalia Hayyu; Eriyanto, Syavira Riski (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2026)
Through innovative technology and pedagogy-based training, this community service program sought to improve the professional competency of vocational English teachers. The primary issue found was the inadequate use of cutting-edge digital technology and student-centered pedagogy in vocational English classrooms, which had an impact on both student engagement and teaching effectiveness. Focus Group Discussions (FGD), seminars, and workshops were used in a professional development program for fifteen English instructors at SMKN 2 Palembang in order to address this problem. Teachers were able to investigate technology-enhanced learning platforms, creative teaching methods, digital assessment tools, and vocational-context English education through the program's collaborative and participatory techniques. Observations, interviews, surveys, and reflective assessment sheets were used to gather data. The results showed that teachers' comprehension and practical abilities in incorporating cutting-edge technology and pedagogy into classroom activities had considerable improvement from 13.33% before the training to 86.67% after the training. Teachers showed greater assurance when utilizing digital technologies to create interactive, student-centered learning resources. The sustainability of technology-based professional development programs was positively perceived by the participants. The program came to the conclusion that innovative technology and pedagogy-based training successfully enhanced the professional competency of vocational English teachers and promoted more flexible, interesting, and pertinent English learning strategies in vocational education settings.